“Control de stemphylium oslani en tomate utilizando extractos de paico, barbasco, huamanzamana y carambola en la provincia de San Martín” - Tuesta Reátegui, Iván (2005)
The present investigation work was carried out in order to evaluate and to compare the effectiveness of the extracts of Lonchocarpus utilís, Averrhoa carambola, Jacaranda copaía and Chenopodíum ambrosioídes with three witness (two fungicidas and without fungicida) to determine the effectiveness, to reduce the incidence and severity of the stain to foliate caused by the mushroom Stemphylíum solaní and the effects in the plant of the tomato under conditions of gavels. The present investigation work was executed in the Laboratory of Vegetable Sanity - Fitopatología of the Ability of Agrarian Sciences, located at 06° 29 '40", of the South Latitude, 76° 27 ' 55 of the Longitude West and 295 m.s.n.m.m. of altitud.Fue driven totally at random under design with 11 treatment with 4 tests. The extract of Lonchocarpus utilis to the dose 20 mi for liter of water had better effect fungico for the control of the Stemphylium solanífor that it showed smaller number of stains (17), incidence (42, 11 %), severity (17,37 %) and bigger effectiveness (71,93 %) with regard to the patógeno; and the positive effect of the cultivation of the tomato. The biggest heights (65, 12 and 66,20 cm) and bigger numbers of fruits (7,51 for plant) they were obtained with applications from Lonchocarpus utilís to 20 and 40 mili. Ali the studied extracts showed to have behavior fungitóxico, against Stemphylíum solaní. The biggest quantity in floral bellboys and flowers for plant were obtained with Chenompodíum ambrosíoides to 40 mili of water registering 24, 11 and 18,92 respectively, but it doesn't show good effectiveness like fungicide. The effects of the leaves of Carom and Paico with regard to the incidence, effectiveness and effect in the plant show very marked variation.